Franchise Business Sustainability – West Java Province Small Medium Enterprises - Lilian Danil; Nina Septina (Research Report - Humanities and Social Science, 2015)
Entrepreneurship has become a prime stimulant in the economic world, especially in the America, Japan, and Singapore. However, this has not yet occurred in Indonesia, supported by the data from of the Ministry of Cooperatives and Small and Medium Enterprises which mentioned about the number of Indonesian entrepreneurs which only 1.9 percent of 250 million inhabitants in 2013. Franchise business which is growing in Indonesia has a great opportunity for small and medium enterprises business development. Therefore, in increasing number of entrepreneurs, creativity and innovation play a great role in running the sustainable bussiness.The research’s object is examining the perpetrators franchise small and mediumenterprises in Indonesia region either they still survive or has been paralyzed. This study will use qualitative methods using in-depth observation and interviews. The research results are expected to increase knowledge and enrich the concept of entrepreneurship and franchising as the learning material in the classroom to build the entrepreneurial spirit of small and medium businesses in general and to encourage students in particular to make more advanced nations.Keywords: Franchise, Business sustainability, Indonesia’s Small Medium Enterprises